A Secure Blind Path Energy Aware Geographical Routing Protocol for Wireless Sensor Networks - Manjunath, DR; Thimmaraju, SN (International Journal of Computer Sciences and Engineering, 2019)
Wireless Sensor Networks (WSNs) are rapidly becoming popular due to they are low cost solutions for various realworld challenges. It is widely used in military surveillance, transportation management, health care, etc. Prolonging a wireless sensor network’s lifetime is closely related to energy consumption. Furthermore, secure data transfer is a great challenge for WSNs, especially for applications that use important data such as military applications. The main objective is not only to design a new routing protocol that ensures network lifetime efficiency, but the balance between these security threats and energy efficiency. For that reason, we have designed the standard framework and simplify the process of building a novel geographical routing sensor networks that introduce location privacy, data privacy and energy awareness routing. Firstly, the whole network is divided into multiple grids with randomly distributed sensor nodes and all sensor nodes only communicates with their neighbor grids. Each grid selects the grid head based on the maximum energy level and minimum distance of the destination node in each grid .The data transmitter node identifies the neighbor grid with the grid head having maximum energy level and minimum distance of the destination node among its neighbor grids for data transmission. Further Hybrid AES-DES algorithm is applied to provide data privacy and location privacy. The proposed protocol provides a good trade-off between balancing energy, security and routing efficiency, and in all cases the lifespan of sensory networks can be significantly expanded.